Candidal carriage in saliva and subgingival plaque among smokers and non-smokers with chronic periodontitis—a cross-sectional study - Santhana Krishnan,Gayathri; Naik,Dilip; Uppoor,Ashita; Nayak,Sangeeta; Baliga,Shrikala; Maddi,Abhiram (PeerJ, 2020)
Background and Objectives Studies of gum or periodontal disease have focused mainly on bacterial pathogens. However, information related to fungal species in the saliva and subgingival mileu is particularly lacking in smokers with periodontitis. This cross-sectional study compared the prevalence of various Candida species in saliva and subgingival plaque samples of smokers and non-smokers with periodontal disease. Methodology Study subjects were recruited into three group—Group 1: Smokers with chronic periodontitis (N = 30), Group 2: Non-smokers with chronic periodontitis (N = 30) and Group 3: Healthy controls (N = 30). Clinical parameters recorded included plaque index (PI), gingival index (GI), periodontal probing depth (PPD) and clinical attachment loss (CAL). Saliva and subgingival plaque samples were collected from subjects from the above groups. The collected samples were processed for isolation and identification of various Candida species using CHROMagar chromogenic media. Additionally, antifungal susceptibility tests were performed for the isolated Candida species in order to assess antifungal drug resistance to fluconazole and voriconazole. Results Prevalence of Candida species in saliva samples was quantified as 76.6% in Group 1, 73.3% in Group 2 and 36.6% in Group 3 and statistically significant differences were observed between groups 1 & 3. Prevalence of Candida species in subgingival plaque samples was quantified as 73.3% in Group 1, 66.6% in Group 2 and 60% in Group 3 and no statistically significant differences were observed between groups. Candida albicans was the most frequently isolated species followed by Candida krusei and Candida tropicalis. A positive correlation was observed for smoking exposure, pack years and Candida colonization. A marginally significant positive correlation was observed between Candida colonization and increasing pocket depth and attachment loss. Antifungal drug resistance was mainly observed for Candida krusei in both saliva and subgingival plaque samples. Conclusion Based on the results we can conclude that oral candidal carriage is significantly increased in smokers with periodontal disease. Mechanistic studies are needed to understand the importance of Candida species in periodontal disease.
Keywords: Candida carriage; Periodontitis; Subgingival plaque; Saliva; Smoking